2003
DOI: 10.1002/ajim.10214
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization of families of carpenters with alcohol or substance abuse‐related diagnoses

Abstract: Utilization patterns were influenced to a significant degree by concordant diagnoses among spouses and children. Excess mental health care was seen among families of carpenters with ASRD above their care for substance abuse treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…CSOs with a substance abusing family member are more likely to seek medical services than those without such a family member (12, 13). Medical conditions such as acid-related disorders, asthma, hypertension, and sexually transmitted diseases are reported more frequently by family members who have an SUI relative to those who do not (14).…”
Section: Prevalence and Frequency Of Problems Of Family Members With mentioning
confidence: 99%
“…CSOs with a substance abusing family member are more likely to seek medical services than those without such a family member (12, 13). Medical conditions such as acid-related disorders, asthma, hypertension, and sexually transmitted diseases are reported more frequently by family members who have an SUI relative to those who do not (14).…”
Section: Prevalence and Frequency Of Problems Of Family Members With mentioning
confidence: 99%
“…Having a family member with an alcohol or drug problem affects family functioning and dynamics [1–4] which may lead to increased risk of developing patterns of illness and behavioral problems [5]. A number of studies have shown that family members of alcoholics, or people with an alcohol or drug disorder, have increased prevalence of medical and psychiatric conditions and increased medical cost and utilization, compared to the family members of people without alcohol or drug disorders [5–11]. No studies, however, have investigated how these people compare to the family members of people with other chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For people friendly with a heavy drinker, but not living together with them, the odds were 23% higher compared to individuals not friendly with a heavy drinker ( Bloomfield et al, 2019 ). CSOs are also more likely than others to seek medical services ( Lennox et al, 1992 ; Lipscomb et al, 2003 ) and have healthcare costs 31–70% higher than the people not close to an individual with heavy alcohol or substance use ( Ray et al, 2007 ; Svenson et al, 1995 ). It is, therefore, no surprise that Birkeland et al (2018) , in a scoping review, found that partners of people with problematic alcohol or substance use reported lower quality of life compared to the general population.…”
mentioning
confidence: 99%